P/CAF-mediated spermidine acetylation regulates histone acetyltransferase activity. (3rd November 2016) - Burgio, Giosalba; Corona, Davide F. V.; Nicotra, Concetta M. A.; Carruba, Giuseppe; Taibi, Gennaro
Abstract: Histones and polyamines are important determinants of the chromatin structure. Histones form the core of nucleosome particles and their modification by acetylation of N-terminal tails is involved in chromatin structural changes and transcriptional regulation. Polyamines, including spermidine, are also targets of both cytoplasmic and nuclear acetylation, which in turn alters their affinity for DNA and nucleosomes. Previous studies report the interplay between polyamines metabolism and levels of histone acetylation, but the molecular basis of this effect is still unclear. In this work, we have analyzed the in vitro effect of spermidine on histone H3 acetylation catalyzed by P/CAF, a highly conserved histone acetyltransferase (HAT) (E.C. 2.3.1.48). We have observed that spermidine at very low concentrations activates P/CAF, while it has an inhibitory effect at concentrations higher than 4 μM. In addition, the in vitro bimodal effect of spermidine on histone H3 acetylation was also distinctly observed in vivo on polytene chromosomes of Drosophila melanogaster . We also performed kinetic studies indicating that the activating effect of low spermidine concentrations on P/CAF-HAT activity is based on its involvement as a substrate for P/CAF to produce N 8 -acetylspermidine that is able in turn to increase the enzyme activity up to four fold.